Analysis of confined AAC walls under monotonic compression. (15th February 2022) - Drobiec, Łukasz; Mazur, Wojciech; Rybarczyk, Tomasz
Highlights: Confined masonries are not only made in seismic areas, but very few test results for monotonic-loaded confined walls are still available. The test results of 20 walls showed that the use of confining limits the cracks opening and increases the load-bearing capacity of the wall by about 40%. The lintel stiffness has a significant impact on the load-bearing capacity of the walls. The introduction of additional confining elements at the openings allowed to increase the load capacity of the walls by 30%. Strut&Tie models can be successfully used for calculation of the confined masonry. The calculation method specified in the final draft of second edition of Eurocode 6 has to be more fully described. Abstract: Confined walls are structures frequently encountered in seismic zones. They have been put to numerous tests over time, including entire buildings being tested under cyclic loading. However, the observed trend is that confined masonry structures are also built in areas of little or no seismic activity. The draft 2nd edition of Eurocode 6 even brings about calculation procedures for confined walls erected outside active seismic regions. That said, an insufficient number of tests have still been performed on confined masonry structures under monotonic load, a situation which has a considerable negative impact on the verification process regarding standard recommendations. This paper presents results obtained from tests carried out on 20 walls, both non-confined and with reinforced concrete confinement. The full-scale walls put to tests were built of autoclaved aerated concrete (AAC). They were subjected to one loading cycle until failure. The testing procedure involved numerical simulations and calculations based on data obtained from the strut-and-tie models, as well as calculations carried out in accordance with the procedures laid down in the draft 2nd edition of Eurocode 6. It was demonstrated during the tests that wall confinement has a significant impact on the masonry resistance under monotonic load. The numerical models were used to determine the distribution of stresses in the test walls and to select the effective strut-and-tie model. The authors of the paper also verified the standard recommendations.